Prognostic value of inflammatory markers and clinical features for survival in advanced or metastatic esophageal squamous cell carcinoma patients receiving anti-programmed death 1 treatment - Da, Liangshan; Qu, Ziting; Zhang, Congjun; Shen, Yuanyuan; Huang, Wei; Zhang, Yiyin; Gu, Kangsheng (Frontiers in Oncology, 2023)
Purpose: This study aims to assess the prognostic value of inflammatory markers and clinical features in advanced or metastatic esophageal squamous cell carcinoma (ESCC) patients receiving anti-PD-1 treatment. Methods: Based on receiver operating characteristic curve (ROC) analysis, Youden’s indexes were applied to determine the cut-off values for inflammatory markers, including neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocye ratio (dNLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII). Wilcoxon test was conducted to evaluate the changes in the above inflammatory markers. Kaplan-Meier method was utilized to estimate PFS and OS, and the Log-rank test was used to compare the differences between groups. Univariate and multivariate Cox regression analyses were performed to assess the prognostic value of inflammatory markers and clinical features. Results: 162 advanced or metastatic ESCC patients receiving anti-PD-1 treatment were enrolled in this retrospective study. The cut-off values of NLR, dNLR, MLR, PLR, and SII were 4.748, 2.214, 0.309, 250.505, and 887.895, respectively. NLR, dNLR, PLR, and SII declined significantly among the PR (P<0.001, P<0.001, P=0.036, P<0.001), ORR (P<0.001, P<0.001, P=0.036, P<0.001), and DCR (P<0.001, P<0.001, P=0.038, P<0.001) groups, respectively. Significant increases were found in NLR (P<0.001), dNLR (P<0.001), MLR (P=0.001), and SII (P=0.024) groups when anti-PD-1 treatment failed. Multivariate Cox analyses indicated that NLR (P<0.001, P=0.002), lymph node metastasis (P=0.013, P=0.001), ECOG PS (P=0.008, P=0.002), and treatment lines (P=0.037, P=0.048) were significant prognostic indicators of PFS and OS. Additionally, SII (P=0.016) was also significantly related to OS in ESCC patients. The risk score model showed that low-risk patients prolonged PFS and OS than those with middle or high risk (P<0.001, P<0.001). Conclusion: Inflammation markers can reflect short-term outcomes of anti-PD-1 treatment for ESCC patients. NLR, lymph node metastases, ECOG PS, and treatment lines were significant prognostic indicators for PFS and OS. And the risk score model constructed based on the above factors has favorable prognostic predictive value.